Apoptosis-promoting and migration-suppressing effect of alantolactone on gastric cancer cell lines BGC-823 and SGC-7901 via regulating p38MAPK and NF-κB pathways. (October 2019) - He, Y; Cao, X; Kong, Y; Wang, S; Xia, Y; Bi, R; Liu, J
Background: Gastric cancer is a malignant tumor with high incidence rate and mortality rate. Purpose: In this study, we investigated the anti-cancer effect of alantolactone, a sesquiterpene lactone, on gastric cancer cell lines BGC-823 and SGC-7901. Methods: BGC-823 and SGC-7901 cells were treated with different concentrations of alantolactone, Hoechst 33258 staining, flow cytometry, wound healing assay, invasion assay, colony forming assay, quantative polymerase chain reaction, and western blot analysis were used to evaluate the anticancer activity of alantolactone to gastric cancer. Results: Alantolactone induced apoptosis of gastric cancer cells by regulating the expression of Bax, Bcl-2, and p53, which related to intrinsic apoptotic pathway, and suppressed colony formation, migration, and invasion by mediating the expression of matrix metalloproteinase (MMP)-2, MMP-7, and MMP-9. Cell signaling pathway analysis showed that alantolactone enhanced the phosphorylation of p38 and decreased the translocation of nucleus p65, suggesting that the apoptosis-promoting and migration-suppressing effect of alantolactone might at least partially rely on regulating p38 mitogen-activated protein kinase (p38MAPK) pathway and nuclear factor-κB (NF-κB) pathway. Conclusions: Alantolactone can be used as a potential therapeutic agent for treating gastric cancer.